B110 Evaluating the safety of regional anaesthesia to patients on anticoagulants, with the use of thromboelastography. (11th August 2022) - Iakovou, D; Egan, T
Abstract : Background and Aims: Thromboelastography (TEG) is a testing system designed to monitor the coagulation process in real-time. TEG-guided therapy has been shown to be valuable in a variety of invasive procedures. The utility of TEG currently has unvalidated clinical benefit in the assessment of risk in regional anaesthesia, even though it could prevent potential haematological complications such as extensive haematomas in the nerve sheath or injection site, profound motor signs and nerve damage. The aim of this audit is to assess whether the use of TEG in assessing the risk for regional anaesthesia for lower limb amputations affects the rates of the complications. Methods: In this service evaluation audit, data from the patient information system (Powerchartâ) will be analysed retrospectively and compared with patients recruited prospectively, to whom TEG will be used to assess their coagulation potential. 30 patients from each group will be analysed focusing on a 30-day complication rate due to regional anaesthesia. All patients must have been prescribed and adhered to at least one dose of anticoagulation in the 7-day period before regional anaesthesia is performed. Results: Result will be presented with statistical analysis and their clinical effectiveness will be assessed collectively with the financial consequences on the healthcare provider. Adding TEG to standard regional anaesthesia intervention will be also assessed qualitatively according to the type and frequency of complications presenting. Conclusions: Assessing the use of TEG in standard practice of regional anaesthesia, might lead to implementing a time-saving testing method to prevent future complications from anticoagulant medication.